Leadership Style Overview of Inpatient Unit Leaders at a Military Hospital and a Government Hospital - Rara, Abd Rahman; Nasrullah, Nasrullah; Suntin, Suntin; Hisyam, Muhammad; Mas, Haris Saputra (PT.Mantaya Idea Batara, 2025)
Background: Health is a fundamental human need that requires adequate support from healthcare facilities, including hospitals. The leadership of inpatient unit leaders plays a strategic role in influencing nursing performance and the quality of healthcare services. Military hospitals, characterized by a hierarchical structure and a workforce comprising both military personnel and civilians, differ fundamentally from government hospitals, which are primarily staffed by civilian healthcare professionals. This study aims to analyze the leadership styles of inpatient unit leaders at a Military Hospital (Level II Pelamonia Hospital) and a Government Hospital (RSUD Haji Makassar). Method: This study uses a quantitative approach with a descriptive cross-sectional research design. The sample consists of 98 respondents, equally distributed between Level II Pelamonia Hospital (49 respondents) and RSUD Haji Makassar (49 respondents). Data were analyzed using the chi-square test. Results: The chi-square test results indicate no significant difference in the leadership styles of inpatient unit leaders at Level II Pelamonia Hospital and RSUD Haji Makassar (? = 0.372, ? = 0.05). Therefore, the null hypothesis (H?) is accepted, and the alternative hypothesis (H?) is rejected. Conclusion: There is no statistically significant difference in the leadership styles of inpatient unit leaders at t